Distribution Optimal Power Flow With Energy Sharing Via a Peer-To-Peer Transactive Market - Zheng, Boshen; Fan, Yue; Wei, Wei; Xu, Yourui; Huang, Shaowei; Mei, Shengwei (Frontiers in Energy Research, 2021)
The technology advancement and cost decline of renewable and sustainable energy increase the penetration of distributed energy resources (DERs) in distribution systems. Transactive energy helps balance the local generation and demand. Peer-to-Peer (P2P) energy trading is a promising business model for transactive energy. Such a market scheme can increase the revenue of DERs owners and reduce the waste of renewable energy. This paper proposes an equilibrium model of a P2P transactive energy market. Every participant seeks the maximum personal intertest, with the options of importing or providing energy from/to any other peer across different buses of the distribution network. The market equilibrium condition is obtained by combining the Karush-Kuhn-Tucker (KKT) conditions of all problems of individual participants together. The energy transaction price is endogenously determined from the market equilibrium condition, which is cast as a mixed-integer linear program (MILP) and solved by a commercial solver. The transactive energy flow is further embedded in the optimal power flow problem to ensure operating constraints of the distribution network. We propose a remedy to recover a near optimal solution when the second-order cone relaxation is inexact. Finally, case study demonstrates that proposed P2P market benefits all participants.